2021
DOI: 10.2147/jir.s329972
|View full text |Cite
|
Sign up to set email alerts
|

Maternal High-Fat Diet Programs Renal Peroxisomes and Activates NLRP3 Inflammasome-Mediated Pyroptosis in the Rat Fetus

Abstract: Maternal obesity impairs kidney development and function of the offspring and leads to a greater risk of kidney disease in adulthood. The present study aimed to investigate the link between peroxisomes, oxidative stress (OS), and inflammasomes in the fetal kidney of maternal obesity rats and to explore the potential therapeutic effects of the antioxidant pyrroloquinoline quinone (PQQ). Methods: Maternal obesity rats were developed by administration of a high fat diet plus supplementation with PQQ (40 mg/kg bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In contrast, a study in rats has shown that exposure to maternal obesity in the late-gestation fetus did not affect fetal kidney nephron number (173) . However, there was evidence for increased cellular stress, inflammation and apoptosis in the kidney of fetuses of obese dams compared to healthy controls (173) .…”
Section: Evidence Of Offspring Kidney Dysfunction From Human Studies ...mentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, a study in rats has shown that exposure to maternal obesity in the late-gestation fetus did not affect fetal kidney nephron number (173) . However, there was evidence for increased cellular stress, inflammation and apoptosis in the kidney of fetuses of obese dams compared to healthy controls (173) .…”
Section: Evidence Of Offspring Kidney Dysfunction From Human Studies ...mentioning
confidence: 81%
“…In contrast, a study in rats has shown that exposure to maternal obesity in the late-gestation fetus did not affect fetal kidney nephron number (173) . However, there was evidence for increased cellular stress, inflammation and apoptosis in the kidney of fetuses of obese dams compared to healthy controls (173) . Furthermore, late-gestation proteomic analysis of male fetal mouse kidneys from dams fed with a high-fat diet showed differential expression of proteins linked to transcription/translation, mitochondrial processes and membrane remodelling compared to offspring of controls (174) .…”
Section: Evidence Of Offspring Kidney Dysfunction From Human Studies ...mentioning
confidence: 81%
“…61,62 In terms of mechanism of action, maternal obesity increased apoptosis and pyroptosis in fetal kidneys, with elevated oxidative stress and decreased antioxidant defense. 63 These observations indicate that exposure to intrauterine hyperlipidemia or hyperglycemia impairs renal development and function.…”
Section: Kidneymentioning
confidence: 98%
“…149 Generally, pyroptosis is closely associated with various disorders and adverse pregnancy complications through lytic cell death, cytokines release, auto-antigens release, and dysfunction of organelles. 63,155 At present, a paucity of studies has reported the effect of pyroptosis on offspring outcomes. A recent study showed that maternal obesity reduced the number of peroxisomes and subsequently activated oxidative stress and NLR Family Pyrin Domain Containing 3 (NLRP3) inflammasome-mediated pyroptosis in fetal kidneys.…”
Section: Cell Deathmentioning
confidence: 99%
“…Higher perinatal weights have been observed from as early as postnatal day 1, with faster weight gain, abdominal adiposity, and circulating cholesterol levels thereafter, once further challenged with an HFD [ 66 ]. Maternal obesity has been shown to increase pryoptosis and apoptosis in foetal kidneys, with decreased antioxidants such as superoxide dismutase 2 (SOD2) and catalase and increased oxidative stress marker epoxide hydrolase (Ephx) 2, mediated by the Nod-like receptor protein (NLRP) 3 inflammasome pathways [ 67 ]. Maternal obesity has also been shown to have teratogenic effects on cardiac development, with an increased risk of abnormal aortic valve development, endothelial dysfunction, and abnormal hemodynamic function in offspring [ 68 ].…”
Section: Introductionmentioning
confidence: 99%